The Metallic Nature of Epitaxial Silicene Monolayers on Ag(111). (10th June 2014) - Johnson, Neil W.; Vogt, Patrick; Resta, Andrea; De Padova, Paola; Perez, Israel; Muir, David; Kurmaev, Ernst Z.; Le Lay, Guy; Moewes, Alexander
<x xml:space="preserve">Abstract</x> Silicene is a two‐dimensional structure composed of a buckled hexagonal honeycomb lattice of silicon atoms. Freestanding silicene is yet to be synthesized, but epitaxial silicene monolayers have been directly observed or predicted to exist on a number of supporting substrates. Herein the atomic and electronic structures of five distinct epitaxial silicene morphologies on Ag(111) are examined through the complementary techniques of density functional theory and soft X‐ray spectroscopy at the Si L2, 3 edge. Hybridization with the Ag(111) substrate is shown to cause these silicene monolayers to become strongly metallic, and the specific electronic interactions that are responsible for this metallic nature are determined. The results imply that epitaxial silicene on Ag(111) does not possess the Dirac cone electronic structure that is characteristic of freestanding silicene and graphene sheets.